Toolpath planning for CNC machining of hub surface of blisk. Issue 1 (1st August 2022) - Zhu, Yu; Xiao, Shihong; Wang, Wenli
Abstract: This paper presented a toolpath planning and generating method for machining a hub surface of a blisk. This method can be used to generate smooth and gradually changing toolpaths and avoid an undercut on hub. In this paper, the hub surface has been defined with a u θ -parametric region. Then character curves, character points and extension curves have been solved in the u θ -parametric region. These curves have been employed to define boundaries of a machining region on the hub surface. The machining region parted by the boundaries has been mapped into a ws-parametric region which was applied to plan toolpaths. The method was employed to mill the hub surface of a blisk, and the results indicated that the profile error of the hub was within ±0.02mm after machining. This method has a significant value of practical applications, and the machining precision can satisfy the designing requirement of a blisk.